Measurement of the running of the fine-structure constant - Dova, María Teresa (2000)
Small-angle Bhabha scattering data recorded at the Z resonance and large-angle Bhabha scattering data recorded at 's s189 GeV by the L3 detector at LEP are used to measure the running of the effective fine-structure constant for spacelike momentum transfers. The results are <mtext>α</mtext>−1<mtext>(−2.1</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2<mtext>)−α</mtext>−1<mtext>(−6.25</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2<mtext>)=0.78±0.26</mtext> <mtext>α</mtext>−1<mtext>(−12.25</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2<mtext>)−α</mtext>−1<mtext>(−3434</mtext><mspace sp="0.4" width="2px" linebreak="nobreak" is="true"></mspace><mtext>GeV</mtext>2<mtext>)=3.80±1.29,</mtext> in agreement with theoretical predictions.